Optimizing Pectin Yield From Burmese Grape (Baccaurea ramiflora) Peels Using Box–Behnken Design and Quality Evaluation - Md Akram Hossain; Md. Masud Rana; Mir Tuhin Billah; Md Moinul Hosain Oliver; M. Amdadul Haque (International Journal of Food Science)
Pectin, a polysaccharide, is widely used as a gelling and thickening agent in the food industry. This study undertook optimization of pectin extraction from the peels of Baccaurea ramiflora Lour. (Burmese grape or lotkon), an abundantly grown wild fruit in Bangladesh. We applied the Box–Behnken Design of Response Surface Methodology with varied processing parameters including pH, time, and temperature. The Response Surface Methodology, employing a second-order polynomial model, successfully optimized the extraction conditions for the maximum pectin yield. The model predicted a pectin yield of 10.73%, which closely matched the experimental yield of 10.56%. The optimal conditions for pectin extraction were determined as pH (2.4), extraction time (56 min), and temperature (76°C). Further analyses of the extracted pectin under optimized conditions confirmed its excellent potential for food applications. The pectin was characterized by its moisture content (10.42%), water activity (0.51), ash content (3.41%), equivalent weight (769.23 mg/mole), methoxyl content (7.75%), anhydrouronic acid content (66.88%), degree of esterification (65.79%), and acetyl value (0.39%). These determined parameters strongly support that the pectin extracted from the peels of Burmese grapes is of good quality.